1973
DOI: 10.1161/01.res.33.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Isolated Cerebral and Peripheral Arteries to Serotonin, Norepinephrine, and Transmural Electrical Stimulation

Abstract: Spirally cut strips of cerebral and peripheral arteries from dogs were used for comparing the vasoconstricting effect of serotonin, norepinephrine, K + , and transmural electrical stimulation. Sensitivity of cerebral (basilar, posterior cerebral, and middle cerebral) arterial strips to serotonin was markedly greater than that to norepinephrine with respect to the median effective concentration (ED 30 ) and the maximum response. Contractile responses of isolated human cerebral arteries to serotonin and norepine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
54
1

Year Published

1974
1974
1999
1999

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(61 citation statements)
references
References 32 publications
6
54
1
Order By: Relevance
“…Similar relaxation induced by low concentrations of K+ (5-10 mM) has been demonstrated in isolated human and dog basilar arteries (5). A betaadrenergic mechanism is not involved in the genesis of the relaxation, since propranolol, a beta-adrenergic blocking agent, did not inhibit the relaxation and isoproterenol, a beta agonist, elicited no or only a slight relaxation of basilar arteries even when high concentrations were applied (Toda, unpublished data).…”
Section: -Heksupporting
confidence: 58%
See 1 more Smart Citation
“…Similar relaxation induced by low concentrations of K+ (5-10 mM) has been demonstrated in isolated human and dog basilar arteries (5). A betaadrenergic mechanism is not involved in the genesis of the relaxation, since propranolol, a beta-adrenergic blocking agent, did not inhibit the relaxation and isoproterenol, a beta agonist, elicited no or only a slight relaxation of basilar arteries even when high concentrations were applied (Toda, unpublished data).…”
Section: -Heksupporting
confidence: 58%
“…It appears that 5-hydroxykynurenamine and serotonin share receptors in dog basilar arteries and that the effect of serotonin is specifically antagonized by 5-hydroxykynurenamine. 5-Hydroxykynurenamine (5-HK) was first found in mouse urine by Makino (1), who suggested that it was biologically active (2). Recently, Havaishi and Hirata (3,4) isolated from rabbit brain and intestine a new tryptophan 2,3-dioxygenase which catalyzes the conversion of serotonin to 5-hydroxyformylkynurenamine, the latter being hydrolyzed to 5-HK by formamidase.…”
mentioning
confidence: 99%
“…Regional differences in the response of isolated canine arteries of the dog to vasoconstrictor and dilator agents have been demonstrated (Bohr, Goulet & Taquini, 1961;Toda & Fujita, 1973;Toda, 1974). The relaxant effect of dopamine in different arteries under the same experimental conditions are summarized in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction 5-Hydroxytryptamine (5-HT) is a potent cerebroarterial constrictor (Toda & Fujita, 1973), and is converted by monoamine oxidase to 5-hydroxyindoleacetaldehyde, which is degraded by aldehyde dehydrogenase to 5-hydroxyindoleacetic acid (5-HIAA) or by aldehyde reductase to 5-hydroxytryptophol (5-HTOL). 5-HIAA relaxes isolated cerebral arteries and does not interfere with the contractile response to 5-HT (Toda, Hojo, Sakae & Usui, 1974).…”
mentioning
confidence: 99%